Characterization and Value Assignment of a Monoclonal Antibody Reference Material, NMIJ RM 6208a, AIST-MAB - Kinumi, Tomoya; Saikusa, Kazumi; Kato, Megumi; Kojima, Reiko; Igarashi, Chieko; Noda, Naohiro; Honda, Shinya (Frontiers in Molecular Biosciences, 2022)
Monoclonal antibodies have been established as the largest product class of biopharmaceuticals. Because extensive characterization is required for development and quality control of monoclonal antibody, a widely available reference material (RM) is needed. Herein, a humanized IgG1κ monoclonal antibody reference material, RM 6208-a, AIST-MAB, was established by the National Metrology Institute of Japan, National Institute of Advanced Industrial Science and Technology (NMIJ/AIST). The monoclonal antibody solution was produced as a pharmaceutical grade using a Chinese hamster ovary-derived cell line. The assigned indicative value represents the concentration of the antibody with heterotetrameric structure including oligomeric forms, which has been determined by amino acid analysis using isotope-dilution mass spectrometry, and their homogeneity and stability were assessed. In addition to the antibody concentration, various physicochemical properties including peptide mapping data, charge variants, and aggregates were examined. This RM is intended for use in validation of analytical procedures and instruments such as system suitability test for quantification of antibody. It is also intended for comparing and evaluating the results of antibody analyses across analytical methods and analytical laboratories such as inter-laboratory comparison. Both the material and the set of data from our study provide a tool for an accurate and reliable characterization of product quality attributes of monoclonal antibody in biopharmaceutical and metrology communities.